Enhancing Tropane Alkaloid Production Based on the Functional Identification of Tropine-Forming Reductase in Scopolia lurida, a Tibetan Medicinal Plant - Zhao, Kaihui; Zeng, Junlan; Zhao, Tengfei; Zhang, Haoxing; Qiu, Fei; Yang, Chunxian; Zeng, Lingjiang; Liu, Xiaoqiang; Chen, Min; Lan, Xiaozhong; Liao, Zhihua (Frontiers in Plant Science, 2017)
Scopolia lurida, a native herbal plant species in Tibet, is one of the most effective producers of tropane alkaloids. However, the tropane alkaloid biosynthesis in this plant species of interest has yet to be studied at the molecular, biochemical, and biotechnological level. Here, we report on the isolation and characterization of a putative short chain dehydrogenase (SDR) gene. Sequence analysis showed that SlTRI belonged to the SDR family. Phylogenetic analysis revealed that SlTRI was clustered with the tropine-forming reductases. SlTRI and the other TA-biosynthesis genes, including putrescine N-methyltransferase (SlPMT) and hyoscyamine 6β-hydroxylase (SlH6H), were preferably or exclusively expressed in the S. lurida roots. The tissue profile of SlTRI suggested that this gene might be involved in tropane alkaloid biosynthesis. By using GC-MS, SlTRI was shown to catalyze the tropinone reduction to yield tropine, the key intermediate of tropane alkaloids. With the purified recombinant SlTRI from E. coli, an enzymatic assay was carried out; its result indicated that SlTRI was a tropine-forming reductase. Finally, the role of SlTRI in promoting the tropane alkaloid biosynthesis was confirmed through metabolic engineering in S. lurida. Specifically, hairy root cultures of S. lurida were established to investigate the effects of SlTRI overexpression on tropane alkaloid accumulation. In the SlTRI-overexpressing root cultures, the hyoscyamine contents were c. 1.7- to 2.9-fold higher than those in control while their corresponding scopolamine contents were likewise elevated. In summary, this functional identification of SlTRI has provided for a better understanding of tropane alkaloid biosynthesis. It also provides a candidate gene for enhancing tropane alkaloid biosynthesis in S. lurida via metabolic engineering.